Efektivitas Penggunaan Fitur Smartphone Android Sebagai Media Pembelajaran Matematika pada Peserta Didik Kelas 10 Di SMA Muhammadiyah 10 GKB-Gresik - Yana Firna Aisiyah (Postulat : Jurnal Inovasi Pendidikan Matematika, 2020)
In the era of industrial revolution of 4.0 it is important for the teacher to be able to use smartphone as learning media. The use of technology which is close to student will make it easier for teachers to create effective learning. There are still many learning process now adays that makes student unable to learn independently, students got difficulties to find the material, student are familiar with the lecture method so as to make students less active in learning. The alternative to the problem is the application of smartphone. The aim of research to determine the effectiveness of the use of smartphone media in learning process of senior high school in SMA Muhammadiyah 10 GKB-Gresik. Effectiveness in learning conducted with smartphone media is viewed from the theory of Moore D. Kenneth in his book, effective learning depends on professional teachers with several indicators. This research was conducted at SMA Muhammadiyah 10 GKB-Gresik. The subjects were students of class 10-MIA 2. The instrument used is an observation sheet taken from 6 indicators of the theory of Moore D. Kenneth. The method used is descriptive method. Data is collected using observation techniques. The results of the study showed that the teacher got a score of 92% with the category very feasible to be called a professional seen from 6 indicators so that the teacher had effective learning using smartphone media. The conclusion is that mathematics class teachers are called professionals with the use of smartphone media in learning mathematics in the 10th grade MIA 2 Muhammadiyah 10 High School GKB-Gresik is effectiveKeywords: Effectiveness, Learning, and Smartphone